Development of puzzle learning media for equivalent fractions for fourth-grade elementary school - Sri Teti Anggraini; Zetra Hainul Putra; Otang Kurniaman (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2022)
The background of this research is the lack of use of mathematics learning media in elementary schools. Therefore, this study aims to develop a puzzle learning media for equivalent fractions that is valid and practical. This study used research and development (R&D) methods with the ADDIE model which consists of 5 stages: analyze, design, development, implementation, and evaluation. The puzzle developed were validated by media and materials experts. The subjects of this study were four fourth-grade elementary school students. The results showed that the validity of the media was 91.15% with a very valid category, and the validity of the material was 79.69% with a valid category. Practicality test with 4 fourth-grade students obtained a percentage of 91.68% with a very practical category. Therefore, the puzzle learning media for equivalent fractions is appropriate to be used as a medium for learning mathematics in fourth grade of elementary school.